Bioactive drimane sesquiterpenoids and aromatic glycosides from Cinnamosma fragrans. Issue 8 (15th April 2017) - He, Dahai; Slebodnick, Carla; Rakotondraibe, L. Harinantenaina
Graphical abstract: Abstract: Phytochemical investigation of the ethyl acetate and methanol extracts of the bark of Madagascan endemic and medicinal plant Cinnamosma fragrans led to the isolation of two drimane sesquiterpene derivatives: cinnafragroside A (1 ) and cinnafragrin E (2 ), two aromatic glycosides: 3, 4, 5-trimethoxyphenol 1- O - β -d -apiofuranosyl-(1→6)- β -d -glucopyranoside (3 ) and 3, 4-dimethoxyphenyl-1- O - β -d -apiofuranosyl-(1→6)- β -d -glucopyranoside (4 ), together with 12 known compounds identified as: helicide (6 ), 1-( α -l -rhamnosyl(1→6)- β -d -glucopyranosyloxy)-3, 4, 5-trimethoxybenzene (7 ), vanilloloside (8 ), cinnamadin (9 ), ugandensolide (10 ), cinnamosmolide (11 ), cinnamolide (12 ), polygodial (13 ), cinnamodial (14 ), bemadienolide (15 ), 4-isopropyl-6-methyl- α -tetralone (16 ), and capsicodendrin (17 ). Another new compound, 11-norcinnafragrolide-9-one (5 ), was obtained during chemical derivatization of capsicodendrin and gave a hint to understanding the structure required for the antiproliferative activity of17 . The structures of the new compounds were elucidated based on the interpretation of their spectroscopic data including one and two dimensional nuclear magnetic resonance (1D- and 2D-NMR) and mass spectroscopic data. All isolated compounds were evaluated against the hormone dependent breast cancer cell line MCF-7. Compound17 exhibited the most potent activity with an IC50 value of 0.6 μM. Our preliminary SAR study showed that the hydroxyl group at C-12′ and the presence of conjugated carbonyl contribute to the antiproliferative activity.